Marginal affections in contexts of armed violence: notes on the experience of dwellers in Maré - Ribeiro, Eduardo; Oliveira, Eduardo Moura; Ramos Junior, Eduardo (Plural, 2023)
The paper investigates the emotional experiences of residents in Maré, a Brazilian complex of slums, and how they are influenced by exposure to armed violence. The concept of “marginal affections” in the study encompasses different social markers, reflecting situations of exclusion, structural barriers, and forms of discrimination, stigmatization, and inequality. In this sense, it examines how certain types of affections (such as distrust and fear, sadness and anger, distress) vary according to the personal level of exposure to armed violence. The article also briefly discusses the affectivities inscribed in different types of criminal governance. Employing a descriptive and exploratory approach, the empirical analysis utilizes quantitative data from the research project “Building the Barricades: social impacts of exposure to armed violence in Maré” to provide a socioemotional overview of this population. The paper also puts forth hypotheses concerning emotional and relational figurations of individuals residing in conflict-affected areas and peripheral territories in Brazil, such as the Maré slums in Rio de Janeiro.